Odpowiedź :
1)
[tex]\left \{ {{3x+y=3\ |*3} \atop {2x-3y=2}} \right. \\\left \{ {{9x+3y=9} \atop {2x-3y=2}} \right|+\\\left \{ {{11x=11\ |:11} \atop {2x-3y=2}} \right. \\\left \{ {{x=1} \atop {2*1-3y=2}} \right. \\\left \{ {{x=1} \atop {-3y=0\ |:(-3)}} \right. \\\left \{ {{x=1} \atop {y=0} \right.[/tex]
2)
[tex]\left \{ {{3x-2y=1\ |*3} \atop {5x+6y=11}} \right. \\\left \{ {{9x-6y=3} \atop {5x+6y=11}} \right|+\\\left \{ {{14x=14\ |:14} \atop {5x+6y=11}} \right. \\\left \{ {{x=1} \atop {5*1+6y=11}} \right. \\\left \{ {{x=1} \atop {6y=6\ |:6}} \right. \\\left \{ {{x=1} \atop {y=1} \right.[/tex]
3)
[tex]\left \{ {{x-4y=3} \atop {2x+y=15\ |*4}} \right. \\\left \{ {{x-4y=3} \atop {8x+4y=60}} \right|+\\\left \{ {{9x=63\ |:9} \atop {x-4y=3}} \right. \\\left \{ {{x=7} \atop {7-4y=3}} \right. \\\left \{ {{x=7} \atop {-4y=-4\ |:(-4)}} \right. \\\left \{ {{x=7} \atop {y=1}} \right.[/tex]
4)
[tex]\left \{ {{-3x+2y=-7\ |*(-1)} \atop {5x+2y=1}} \right. \\\left \{ {{3x-2y=7} \atop {5x+2y=1}} \right|+\\\left \{ {{8x=8\ |:8} \atop {5x+2y=1}} \right. \\\left \{ {{x=1} \atop {5*1+2y=1}} \right. \\\left \{ {{x=1} \atop {2y=-4\ |:2}} \right. \\\left \{ {{x=1} \atop {y=-2}} \right.[/tex]
5)
[tex]\left \{ {{x+y=2} \atop {2x-y=4}} \right|+\\\left \{ {{3x=6\ |:3} \atop {2x-y=4}} \right. \\\left \{ {{x=2} \atop {2*2-y=4}} \right. \\\left \{ {{x=2} \atop {-y=0}} \right. \\\left \{ {{x=2} \atop {y=0}} \right.[/tex]
6)
[tex]\left \{ {{x+y=1} \atop {-x+2y=2}} \right|+\\\left \{ {{3y=3\ |:3} \atop {x+y=1}} \right. \\\left \{ {{y=1} \atop {x+1=1}} \right. \\\left \{ {{y=1} \atop {x=0}} \right.\\\left \{ {{x=0} \atop {y=1}} \right.[/tex]